Characterization on three-dimensional trajectory of disk-like gold-nickel-platinum nanomotor using digital holographic imaging - Hu, Liangxing (2019)
Self‐propelling disk‐like nanomotor consisting of three metallic segments: a non‐catalytic gold (Au), central magnetic nickel (Ni), and a catalytic platinum (Pt), is designed and fabricated with a high‐efficiency layer‐by‐layer (LbL) deposition method based on the nano‐electro‐mechanical systems (NMES) technology. A bubble propulsion mechanism, resulting from bubble growth and collapse, is proposed to explain the locomotion of the nanomotor suspended in hydrogen peroxide (H2O2) solution. The autonomous propulsion of Au‐Ni‐Pt nanomotor is characterized by digital holographic imaging and analyzed using Matlab, revealing that oxygen (O2) bubbles are generated and detached from the surface of Pt. In addition, the holographic images are for the first time used to reconstruct the instantaneously three‐dimensional (3D) location and trajectory of the nanomotor.